(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This comprehensive article offers a detailed exploration of the development of American literature, tracing its evolution from the colonial period to the present day. Through a chronological lens, the article highlights key historical moments, literary movements, and influential figures that have shaped the trajectory of American literary expression. From the Puritan writings of the colonial era to the modernist experimentation of the 20th century, the article provides a nuanced understanding of the diverse voices and themes that have contributed to the richness of American literature. Additionally, the article acknowledges the impact of social and cultural factors, such as multiculturalism and technological advancements, on the evolution of American literature. Through its insightful analysis and engaging prose, this article serves as a valuable resource for scholars, students, and enthusiasts seeking to deepen their understanding of American literary history.